Experimental examination of main cutting force and surface roughness depending on cutting parameters - Korkut, Ihsan (Strojniški vestnik, 2008)
Main cutting forces acting on cutting tool depending on cutting parameters when machining AISI 1117 steel were examined experimentally. Experimental results obtained were compared with the empirical results. For the experimental studies, a Kistler 9257A three component (Fc, Ff and Fp) piezoelectric dynamometer was used to measure cutting forces. This dynamometerwas associated with a 5019 B130 charge amplifier connected to a PC running Kistler Dynoware force measurement software. The empirical results were obtained through Kienzle approach. Five different cutting speeds, five different feed rates and two different depth of cuts were used in the experiments. It was observed that cutting forces decreased as the cutting speed increased and increased by the feed rate. Experimental results also showed similar trends with the empirical results. At the end of experiments, it was observed that surface quality increased by with increasing cutting speed and decreased with increasing feed rate.
Keywords: rezanje; sile; hitrost; jeklo; hrapavost